A Semiotics of Multimodality and Signification in the Divine Comedy. - De Benedictis, Raffaele. (Taylor & Francis Group, 2023)
Semiotics and multimodality combined together create new forms of signification in the Divine Comedy. It contributes to the advancement of Dante Studies, Literary Criticism, Multimedia/Multiliteracy, philosophy of language, communication, and education.